Strategic Management Insights into Housewives Consumptive Shopping Behavior in the Post COVID-19 Landscape - Purnama, Suryari; S Bangun, Cicilia (Pandawan, 2024)
Digital wallets can be accessed using a mobile phone Apart from that, marketplace users are used as a tool to make it easier for consumers to shop online. One of the reasons why marketplaces are famous is because of their ease and comfort in use. This research aims to see the influence of digital wallets and marketplace use on consumer shopping behavior among housewives after the Covid 19 pandemic.The population is housewives in DKI Jakarta, with data collection techniques distributing questionnaires to a sample of 113 housewives. Sampling withpurposive sampling, has criteria: respondents are limited to only housewives who are at least 18 years old, respondents have income worth ≤ IDR 5 million and respondents have used marketplaces and digital wallets and are domiciled in DKI Jakarta. Data processing used multiple regression analysis to obtain Y = 0.290 + 0, 139X1 + 0, 576X2 + c. From this equation it is obtained: 1. There is no influence of digital wallets on consumptive shopping behavior among housewives after the Covid 19 pandemic, 2 There is an influence of the marketplace on consumptive shopping behavior among housewives after the Covid 19 pandemic, 3 There is an influence of digital wallets and marketplaces on consumerist shopping behavior among housewives after the Covid 19 pandemic.